Sosialisasi Keamananan Pangan dan Kosmetika pada Warga Aisyiyah Palangka Raya - Agustinawati Umaternate; Wahyu Puspita Dewi; Widya Ayu Valentiningtyas (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
This activity is expected to help government performance in providing information on food and cosmetics that are safe to the community, especially mothers, so that the highest degree of public health can be realized. One of them was carried out by the Universitas Muhammadiyah Palangkaraya through the Community Service program. This activity is expected to help government performance in providing information on food and cosmetics that are safe to the community, especially mothers so that the highest degree of public health can be realized. The Aisyiyah Regional Administrators of Palangka Raya work on average outside the home as employees, teachers, private sector, and others. Households as the smallest community base need to get good guidance and primary attention, because national development relies on the success of human development, where the factors that influence one of them is the availability of safe and quality food. The method of implementing activities uses methods of counseling/awareness and education, as well as inspection simulations on Food Additives and cosmetics that do not meet the requirements. The purpose of this activity is to protect the family against Food Additives and cosmetics that do not meet health requirements. The family is the smallest community that plays a major role in determining the decision-making in nutritional intake every day and what cosmetics can be used by their families are housewives, so education and coaching for mothers is absolutely necessary.